The Use of a Mobile Learning Management System at an Online University and Its Effect on Learning Satisfaction and Achievement - Shin, Won Sug; Kang, Minseok (International Review of Research in Open and Distributed Learning, 2015)
This study investigates online students’ acceptance of mobile learning and its influence on learning achievement using an information system success and extended technology acceptance model (TAM). Structural equation modeling was used to test the structure of individual, social, and systemic factors influencing mobile learning’s acceptance, and how said acceptance influences learning satisfaction and achievement. Unlike earlier TAM-related research that did not provide a broad view of technological acceptance and its impact on learning activities, the present study’s results highlight the relationship between behavioral intention/learning satisfaction and learning achievement. Additionally, this study tests the theoretical model of successful mobile learning by empirically accepting mobile learning management systems. The findings further imply that students at online universities have started to accept mobile technology as a new learning tool; consequently, its acceptance has influenced their learning achievement both directly and indirectly. These discoveries should facilitate a better understanding of students’ usage of mobile learning systems in higher education, and provide timely guidance for its development and implementation.